Adaptability and stability of corn genotypes for baby corn production via GGE biplot and REML - Maxwel Rodrigues Nascimento; Josefa Grasiela Silva Santana; Paulo Ricardo dos Santos; Rogério Figueiredo Daher; Alexandre Gomes de Souza; Ana Kesia Faria Vidal; Moisés Ambrósio; Gérsia Gonçalves de Melo (Acta Scientiarum: Agronomy)
Owing to the interaction between genotype and environment (G × E), selecting and developing high-yielding varieties with strong phenotypic adaptability and stability is paramount. Therefore, this study aimed to determine the efficiency of selection of corn genotypes for baby corn production based on productivity, adaptability, and stability. Eleven corn genotypes were evaluated in six municipalities in the state of Espírito Santo, Brazil in 2019. Superior genotypes were selected using the harmonic mean of the relative performance of the predicted genetic values (HMRPGV) and graphical analysis using the genotype main effect plus G × E (GGE) interaction biplot. Genotypes AG 1051 and BR 106 exhibited the best performance across environments. The HMRPGV method and ideotypes obtained through graphic analysis proved effective in selecting genotypes with high productive potential, responsiveness to environmental changes, and highly predictable behavior in the face of environmental stimuli.